2014
DOI: 10.1007/s13181-014-0451-y
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Rhabdomyolysis in Sympathomimetic Toxicity: a Comparison of Stimulants

Abstract: Synthetic cathinones have emerged as popular drugs of abuse and produce sympathomimetic toxicity. It is unknown if rhabdomyolysis occurs more frequently following the use of synthetic cathinones compared to other stimulants. This retrospective study sought to determine the prevalence of rhabdomyolysis in patients with sympathomimetic toxicity and compare rates among patients using specific agents. Patients greater than 14 years of age with sympathomimetic toxicity and detection of a stimulant agent in urine vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 13 publications
1
21
0
1
Order By: Relevance
“…One clue that a person with hyperthermia and tachycardia might be using these drugs is acute kidney injury secondary to rhabdomyolysis. In a similar manner to cocaine, MDMA, cathinone derivatives, synthetic cannabinoids, and piperazine derivatives may cause rhabdomyolysis and acute kidney injury by increasing skeletal muscle use and metabolic demand while also causing vasoconstriction, resulting in hypoperfusion and poor heat dissipation [12,34]. Tachycardia, agitation and chest pain can also be seen in persons exposed to clenbuterol (β 2 -agonist similar in chemical structure ephedrine), which is used illicitly by bodybuilders to increase muscle mass and lose weight and also used as a bulking agent for heroin [23,24].…”
Section: Sepsis-like Syndromesmentioning
confidence: 99%
“…One clue that a person with hyperthermia and tachycardia might be using these drugs is acute kidney injury secondary to rhabdomyolysis. In a similar manner to cocaine, MDMA, cathinone derivatives, synthetic cannabinoids, and piperazine derivatives may cause rhabdomyolysis and acute kidney injury by increasing skeletal muscle use and metabolic demand while also causing vasoconstriction, resulting in hypoperfusion and poor heat dissipation [12,34]. Tachycardia, agitation and chest pain can also be seen in persons exposed to clenbuterol (β 2 -agonist similar in chemical structure ephedrine), which is used illicitly by bodybuilders to increase muscle mass and lose weight and also used as a bulking agent for heroin [23,24].…”
Section: Sepsis-like Syndromesmentioning
confidence: 99%
“…All of the cases with accompanying laboratory results exhibited high creatine kinase levels, a symptom which is often associated with rhabdomyolysis after synthetic cathinone intoxication. O'Conner et al40 showed that the risk for rhabdomyolysis is greater after synthetic cathinone administration when compared to other stimulant drugs of abuse. It is noteworthy that the fatal case of N-ethylnorpentylone overdose described here had diffuse alveolar hemorrhage which likely contributed to death.…”
mentioning
confidence: 99%
“…Rhabdomyolysis is thought to be multifactorial and related to possible overuse of skeletal muscles as a result of excited delirium or repetitive behaviours as well as extreme vasoconstriction. 14…”
Section: Resultsmentioning
confidence: 99%